Peningkatan Kualitas Pelatihan Dengan Metode Servqual dan Quality Function Deployment: Studi Kasus di Perusahaan Reasuransi - Zarica Halimmah (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
PT. Reinsurance Indonesia Utama (Persero) is the first reinsurance company of the government (BUMN). As a company that is very concerned about their employees, PT. Reinsurance Indonesia Utama (Persero) intensively held some training for their employee. But unfortunately, there is no evaluation regarding the satisfaction of the participants. Therefore, this research was conducted to determine the level of participant satisfaction using the ServQual method and proceed with using the Importance-Performance Analysis (IPA) method to determine the attributes that need improvement. After knowing the attributes that need improvement, the research continuing with QFD method to find out the improvement efforts that need to be done. The questionnaire was used as a data collection method and involved 70 respondents from PT. Reinsurance Indonesia Utama (Persero). The results of ServQual method showed that all attributes tested were negative. This indicates that the services provided have not satisfied the participants. The study continued with the IPA method and obtained 5 attributes in quadrant A that needed improvement. The five attributes are then spelt out in the HOQ matrix and obtained 6 technical responses as the company's response to the participants' needs.